Particle-to-PFU ratio of Ebola virus influences disease course and survival in cynomolgus macaques - Alfson, Kendra J; Avena, Laura E; Beadles, Michael W; Staples, Hilary; Nunneley, Jerritt W; Ticer, Anysha; Dick, Jr, Edward J; Owston, Michael A; Reed, Christopher; Patterson, Jean L; Carrion, Jr, Ricardo; Griffiths, Anthony (Journal of virology, 2015)
This study addresses the role of Ebola virus (EBOV) specific infectivity in virulence. Filoviruses are highly lethal, enveloped, single-stranded negative-sense RNA viruses that can cause hemorrhagic fever. No approved vaccines or therapies exist for filovirus infections, and infectious virus must be handled in maximum containment. Efficacy testing of countermeasures, in addition to investigations of pathogenicity and immune response, often requires a well-characterized animal model. For EBOV, an obstacle in performing accurate disease modeling is a poor understanding of what constitutes an infectious dose in animal models. One well-recognized consequence of viral passage in cell culture is a change in specific infectivity, often measured as a particle-to-PFU ratio. Here, we report that serial passages of EBOV in cell culture resulted in a decrease in particle-to-PFU ratio. Notably, this correlated with decreased potency in a lethal cynomolgus macaque (Macaca fascicularis) model of infection; animals were infected with the same viral dose as determined by plaque assay, but animals that received more virus particles exhibited increased disease. This suggests that some particles are unable to form a plaque in a cell culture assay but are able to result in lethal disease in vivo. These results have a significant impact on how future studies are designed to model EBOV disease and test countermeasures. Ebola virus (EBOV) can cause severe hemorrhagic disease with a high case-fatality rate, and there are no approved vaccines or therapies. Specific infectivity can be considered the total number of viral particles per PFU, and its impact on disease is poorly understood. In stocks of most mammalian viruses, there are particles that are unable to complete an infectious cycle or unable to cause cell pathology in cultured cells. We asked if these particles cause disease in nonhuman primates by infecting monkeys with equal infectious doses of genetically identical stocks possessing either high or low specific infectivities. Interestingly, some particles that did not yield plaques in cell culture assays were able to result in lethal disease in vivo. Furthermore, the number of PFU needed to induce lethal disease in animals was very low. Our results have a significant impact on how future studies are designed to model EBOV disease and test countermeasures.